2014
DOI: 10.1155/2014/494835
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Replication of Infectious Bursal Disease Virus in the DF-1 Cell Line and Chicken Embryo Fibroblasts

Abstract: Infectious bursal disease virus (IBDV) causes a highly contagious disease in young chicks and leads to significant economic losses in the poultry industry. To determine a suitable cell line for IBDV infection, replication, and growth kinetics of the virus, DF-1 cells and chicken embryo fibroblasts (CEF) were used. The population doubling per day (Pd/D) was found to be higher in DF-1 as compared to CEF cells. A suitable time of infection (TOI) was established for increased production of virus and greater infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 29 publications
(31 reference statements)
3
26
0
Order By: Relevance
“…IBD virus (IBDV) was adapted in chicken embryo fibroblast (CEF) cultures. The DF1 cells and maintenance, IBDV propagation and harvesting procedure were described previously by Rekha et al (2014).…”
Section: Antifungal Activitymentioning
confidence: 99%
“…IBD virus (IBDV) was adapted in chicken embryo fibroblast (CEF) cultures. The DF1 cells and maintenance, IBDV propagation and harvesting procedure were described previously by Rekha et al (2014).…”
Section: Antifungal Activitymentioning
confidence: 99%
“…Several cell lines are in use in the development of cell culture-based vaccines among which there are Vero [ 12 , 13 ], CHO [ 12 , 14 ], RK-13 (Rinaldi et al ., 1972), and BGM-70 cells [ 12 , 14 , 15 ]. Several cell lines were utilized for producing IBD vaccines in a cell culture-based system [ 16 , 17 ]. The cell line BGM-70 derived from baby grivet monkey was reported to support the growth and rapidly attenuate classical, variant, and very virulent IBDV strains and with high viral titer [ 6 , 15 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] showed that the proper time for administration of the vaccine is 18 days post hatch with the management conditions in place at the farm. As this disease has been focused in recent reviews regarding its causative agent [ 17 ] and the vaccination [ 18 , 19 ], the present study is, therefore, mainly inclined toward the timely and reliable diagnosis of this threatening disease using gross, histopathology (HP), immunohistochemistry (IHC), and immunofluorescent methods.…”
Section: Introductionmentioning
confidence: 99%